Government Policy on Macroeconomic Stability: Case for Low- and Middle- Income Economies - Oleksii LYULYOV; Tetyana PIMONENKO; Aleksy KWILINSKI; Yana US; Olena AREFIEVA; Oleksandr AKIMOV; Denys PUDRYK (Communications of International Proceedings, 2020)
This study summarizes the existing world experience on scientific and methodological approaches for assessing the macroeconomic stability of the national economy.  The systematization of the scientific background allowed concluding the absence of unitized terminological apparatus to define the concept of macroeconomic stability. This study aims to develop the methodology of integrated assessment of the level of macroeconomic stability of the national economy under improving its conceptual bases. The object of this study is country Ukraine, its neighbour countries and countries that have recently joined the EU. For data processing, the authors used the program of statistical analysis Stata 14. The analysis of macro stability indicators was conducted at different stages of the economic cycle: 1) pre-crisis period (2000–2006); 2) crisis period (2007–2010); and 3) the post-crisis period (2011–2017). The authors proposed the methodology for the integrated assessment of the level of macroeconomic stability of the national economy based on the concept of the pentagon model of macroeconomic stability. Therefore, this model considered five main guidelines of state stabilization policy as follows: 1) GDP growth; 2) unemployment rate; 3) inflation rate; 4) external debt; 5) state budget balance. The obtained results of testing the proposed approach for assessing the level of macroeconomic stability allowed concluding that the largest level of decline in the static indicator of macroeconomic stability of the national economy in 2011-2017 was in Ukraine and Serbia. The authors noted that results of this study are considered to be the base for future investigations aimed at improving the conceptual bases of integrated assessment of the level of macroeconomic stability of the national economy.
Keywords: Macroeconomic Stability; Economic Growth; Index of Macroeconomic Stability; Pentagon Model